IMPLEMENTASI NILAI AYAT-AYAT TARBAWI DALAM PEMBELAJARAN PENGENALAN AGAMA ISLAM DI TK ABA GUMAWANG - Sulaiman, Muh Andi (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
Abstract This study is motivated by the importance of instilling Qur’anic values from an early age as a foundation for the development of children’s character and spirituality. TK ABA, as an Islamic early childhood education institution, plays a strategic role in implementing the educational values of ayat-ayat tarbawi within Islamic Religious Education (IRE) learning in a contextual manner that is appropriate to children’s developmental stages. However, the implementation of ayat-ayat tarbawi values in classroom practice still requires systematic academic investigation. This study aims to describe the implementation of ayat-ayat tarbawi values in Islamic Religious Education learning at TK ABA and to identify the educational values internalized by the students. This research employed a qualitative approach with a descriptive research design. The research subjects consisted of Islamic Religious Education teachers and the principal of TK ABA, while the object of the study was the IRE learning process. Data were collected through observation, interviews, and documentation, and analyzed using an interactive analysis model involving data reduction, data display, and conclusion drawing. The findings indicate that the implementation of ayat-ayat tarbawi values at TK ABA is carried out through habituation activities, teachers’ role modeling, thematic learning, and the use of play-based and Islamic storytelling methods. The main values instilled include monotheism (tawhid), noble character (akhlaq al-karimah), discipline, and gratitude. In conclusion, the implementation of ayat-ayat tarbawi values in Islamic Religious Education learning at TK ABA has been effectively conducted and is relevant to the characteristics of early childhood learners, contributing positively to the development of children’s Islamic character.